In situ synthesis of Fe-doped CrOOH nanosheets for efficient electrocatalytic water oxidation. (20th April 2021) - Gao, Min; Ma, Ning; Yu, Cuiping; Liu, Yu
Abstract: The oxygen evolution reaction (OER) is a process in electrochemical water splitting with sluggish kinetics that needs efficient non-noble-metal electrocatalysts. There have been few studies of CrOOH electrocatalysts for water oxidation due to their low performance. Herein, in situ synthesized Fe-doped CrOOH nanosheets on Ni foam (Fe-CrOOH/NF) were designed as electrocatalysts and performance in the OER was obviously improved. The effect of the amount of Fe doping was also investigated. Experiments revealed that the best performance of Fe-CrOOH/NF requires low overpotentials of 259 mV to reach 20 mA cm −2 together with a turnover frequency of 0.245 s −1 in 1.0 M KOH, which may suggest a new direction for the development of Fe-doped OER electrocatalysts.